First, use this rule of exponents to eliminate the outer exponent for the term on the left:
#(x^color(red)(a))^color(blue)(b) = x^(color(red)(a) xx color(blue)(b))#
#(-y^color(red)(3)z^color(red)(3))^color(blue)(3)(x^4y^2z^3) =>#
#(-y^(color(red)(3)xxcolor(blue)(3))z^(color(red)(3)xxcolor(blue)(3)))(x^4y^2z^3) =>#
#(-y^9z^9)(x^4y^2z^3)#
Next, rewrite the expression as:
#x^4(-y^9y^2)(z^9z^3)#
Now, use this rule of exponents to complete the multiplication:
#x^color(red)(a) xx x^color(blue)(b) = x^(color(red)(a) + color(blue)(b))#
#x^4(-y^color(red)(9)y^color(blue)(2))(z^color(red)(9)z^color(blue)(3)) =>#
#x^4(-y^(color(red)(9)+color(blue)(2)))z^(color(red)(9)+color(blue)(3)) =>#
#x^4(-y^11)z^12 =>#
#-x^4y^11z^12 =>#